Sabotage in Contests: An Overview - J. Atsu Amegashie (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper reviews the relatively small literature on sabotage in contests. It looks at both the formal game-theoretic literature and the empirical and experimental literatures. The treatment is intended to be intuitive with minimal use of technical jargon.
Keywords: D71; 330; contests; sabotage; productive effort